2020
DOI: 10.1371/journal.pone.0238940
|View full text |Cite
|
Sign up to set email alerts
|

Novel genes associated with folic acid-mediated metabolism in mouse: A bioinformatics study

Abstract: Folic acid plays an essential role in the central nervous system and cancer. This study aimed to screen genes related to folic acid metabolism. Datasets (GSE80587, GSE65267 and GSE116299) correlated to folic acid were screened in the Gene Expression Omnibus. Weighed gene co-expression network analysis was performed to identify modules associated with sample traits of folic acid and organs (brain, prostate and kidney). Functional enrichment analysis was performed for the eigengenes in modules that were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Aberrant expression of TRMU is likely pathogenic to humans early in life, as variants in TRMU have been linked to several disease phenotypes, including infantile liver failure 33 , and infantile reversible cytochrome c oxidase deficiency 34 . Next, TTC38 , implicated through the TWAS, has been posited as a factor associated with kidney development 35 , while CELSR1 is highly prevalent in embryonic tissues 36 , 37 and linchpins embryonic development across humans and other vertebrates 38 , 39 . The genes we have outlined here span a diverse set of functions, however we speculate that an underlying commonality is that they act as important contributors to early development.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expression of TRMU is likely pathogenic to humans early in life, as variants in TRMU have been linked to several disease phenotypes, including infantile liver failure 33 , and infantile reversible cytochrome c oxidase deficiency 34 . Next, TTC38 , implicated through the TWAS, has been posited as a factor associated with kidney development 35 , while CELSR1 is highly prevalent in embryonic tissues 36 , 37 and linchpins embryonic development across humans and other vertebrates 38 , 39 . The genes we have outlined here span a diverse set of functions, however we speculate that an underlying commonality is that they act as important contributors to early development.…”
Section: Discussionmentioning
confidence: 99%
“…Wang and colleagues have shown that FA blocked ethanol‐induced teratogenesis, with up‐regulated Hoxa1 and down‐regulated miR‐10a (Wang et al, 2008). It has been suggested that genes, including miR‐185, Ttc38, Sema3A, Insl3, Dll1, Msh4 and Snai1, were the novel factors that may be related with the development of the kidneys and associated to FA treatment (Zhao et al., 2020). It was also suggested that FA protected neuronal cells against apoptosis by preventing the downregulation of miR‐19 and modulation of miR‐19 related downstream PTEN/AKT/p53 pathway (Zhu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%